Ark shell protein hydrolysates inhibit adipogenesis in mouse mesenchymal stem cells through the down-regulation of transcriptional factors. Issue 11 (18th January 2017) - Hyung, Jun-Ho; Ahn, Chang-Bum; Je, Jae-Young
Abstract : Anti-adipogenic peptides were generated from ark shell protein by enzymatic hydrolysis. Abstract : Bioactive peptides have positive effects on human health, including antioxidant, antihypertensive, and antimicrobial. The aim of this study is to produce anti-adipogenic bioactive peptides from ark shell protein and to evaluate the mechanisms that inhibit adipogenesis in mesenchymal stem cells (MSCs). Exposure of ark shell protein hydrolysates (ASPH) produced at a pepsin/substrate ratio of 1 : 500 to 240 min hydrolysis led to a decrease in the intracellular lipid accumulation and increase in lipolysis. Molecular weight fractionation revealed that ASPH III exerts the highest inhibitory effect on the intracellular lipid accumulation and increases lipolysis. At the molecular level, ASPH III significantly inhibits adipogenesis by down-regulating the adipocyte-specific protein expression including peroxisome proliferator-activated receptor γ (PPAR γ), CCAAT/enhancer-binding protein α (C/EBP α), and sterol regulatory element-binding protein 1c (SREBP 1c), as well as downstream lipoprotein lipase (LPL) and fatty acid synthase (FAS) expression. Moreover, treatment with ASPH III increases hormone-sensitive lipase (HSL) and leptin expression in the differentiated adipocytes from MSCs.